Tuning Li-enrichment in high-Ni layered oxide cathodes to optimize electrochemical performance for Li-ion battery. (August 2019) - Wang, Rui; Qian, Guoyu; Liu, Tongchao; Li, Maofan; Liu, Jiajie; Zhang, Bingkai; Zhu, Weiming; Li, Shuankui; Zhao, Wenguang; Yang, Wenyun; Ma, Xiaobai; Fu, Zhendong; et al.
Abstract: To understand what and how structural properties affect battery performance, and to optimize the structural properties accordingly are of crucial importance to improve the performance of cathode materials for advanced Li-ion batteries. Herein, we investigated the influence of Li-enrichment in Li1+ x (Ni0.8 Co0.2 )1- x O2 transition metal (TM) oxide cathodes, obtained by sintering Ni0.8 Co0.2 (OH)2 precursor with different amount of Li sources. Compared with stoichiometric Li1+ x (Ni0.8 Co0.2 )1- x O2 (i.e. x  = 0, Li:TM = 1:1), the improvements of cycling stability and rate performance were observed in material with moderate degree of Li-enrichment with respect to TMs (i.e. x  = 0.019, Li:TM = 1.04:1). Further increase in Li:TM ratio up to 1.07 diminishes the electrochemical performance. Multi-scale structural characterizations including neutron diffraction and aberration-corrected transmission electron microscopy measurements show that the Li-enrichment leads to a monotonical increase in both Li/Ni exchange ratio and Li slab space. Based on the results, we argue that, in material with moderate Li-enrichment, larger Li slab space can facilitate the diffusion of Li ions and a certain amount of Li/Ni disordering can also mitigate the contraction of layered structure, therefore resulting in an optimized electrochemical performance; while in material with excessive Li:TM ratio, the diffusion path can be partially blocked due to the presence of redundant Ni ions in Li layers. Graphical abstract: In this work, the electrochemical performance of high-Ni layered oxide cathode is optimized by tuning the degrees of Li-enrichment in its lattice structure. The optimized cycling stability and rate performance are associated to the optimized structural properties including moderate values of Li/Ni exchange ratio and Li slab space, which will stabilize structure and facilitate the diffusion of Li ions.Image 1 Highlights: The degree of Li-enrichment in high-Ni layered oxide cathodes is tuned, accompanied with the variation of Li/Ni exchange ratio. Improvements of cycling stability and rate performance were achieved in material with moderate degree of Li-enrichment. Relationship between structural properties and electrochemical performances is clarified by using combined XRD, NPD and HAADF-STEM methods.